REDESAIN LOGO DAN PERANCANGAN CORPORATE IDENTITY PERUSAHAAN MANUFAKTUR SEPATU SANDAL EKA PROMA SEBAGAI UPAYA MENINGKATKAN KERJASAMA ANTAR PERUSAHAAN - Tyas, Dwi Estining; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal ArtNouveau, 2014)
Redesign logo and corporate identity design of the Proma Eka is an effort to highlight the potential of Eka Proma, by strengthening the brand image that the company is increasingly recognized and can convince big companies to make Eka Proma as his business partner in the contract that bound cooperation .The study was conducted by qualitative research method is to take the interview, observation, documentation, and literature to obtain data that is used as the manufacturers support design concepts. The process of redesigning the logo and corporate identity design refers to the concept of "Trust". Furthermore, the concept of "trust" is implemented in the form of creative concepts, communication strategies, and media strategies that have undergone a process of data reduction, data display, and conclusion. The design is expected that the brand image of Eka Proma become stronger so that his name is known in particular known by large companies who require a partner company that has the potential as Eka Proma that they are interested and decided to cooperate with Eka Proma.